Behavioral and Electrophysiological Effects of Transcranial Direct Current Stimulation of the Parietal Cortex in a Visuo-Spatial Working Memory Task - Heimrath, Kai; Sandmann, Pascale; Becke, Andreas; Müller, Notger G.; Zaehle, Tino (Frontiers in Psychiatry, 2012)
Impairments of working memory (WM) performance are frequent concomitant symptoms in several psychiatric and neurologic diseases. Despite the great advance in treating the reduced WM abilities in patients suffering from, e.g., Parkinson’s and Alzheimer’s disease by means of transcranial direct current stimulation (tDCS), the exact neurophysiological underpinning subserving these therapeutic tDCS-effects are still unknown. In the present study we investigated the impact of tDCS on performance in a visuo-spatial WM task and its underlying neural activity. In three experimental sessions, participants performed a delayed matching-to-sample WM task after sham, anodal, and cathodal tDCS over the right parietal cortex. The results showed that tDCS modulated WM performance and its underlying electrophysiological brain activity in a polarity-specific way. Parietal tDCS altered event-related potentials and oscillatory power in the alpha band at posterior electrode sites. The present study demonstrates that posterior tDCS can alter visuo-spatial WM performance by modulating the underlying neural activity. This result can be considered an important step toward a better understanding of the mechanisms involved in tDCS-induced modulations of cognitive processing. This is of particular importance for the application of electrical brain stimulation as a therapeutic treatment of neuropsychiatric deficits in clinical populations.